Harnessing Phenotypic Plasticity to Improve Maize Yields - Kusmec, Aaron; de Leon, Natalia; Schnable, Patrick S. (Frontiers in Plant Science, 2018)
Plants can produce different phenotypes when exposed to different environments. Understanding the genetic basis of these plastic responses is crucial for crop breeding efforts. We discuss two recent studies that suggest that yield plasticity in maize has been under selection but is controlled by different genes than yield.